Supporting Student Mental Health in Higher Education - Stones, Samuel; Glazzard, Jonathan (Positive mental health, 2019)
Student mental health is a key consideration in higher education at the moment with recent reports identifying a major gap in provision by universities and how ill-equipped academics feel to support students. This book addresses these concerns, providing comprehensive guidance and workable evidence-informed strategies and interventions to help those working with students to support them effectively. It is suitable for lecturers, personal tutors, student counsellors, course leaders, heads of department and administration staff with responsibility for student support.